A widespread distinct pattern of cerebral atrophy in patients with alcohol addiction revealed by voxel-based morphometry. Issue 6 (6th November 2006) - Mechtcheriakov, Sergei; Brenneis, Christian; Egger, Karl; Koppelstaetter, Florian; Schocke, Michael; Marksteiner, Josef
Abstract : Background: Patients with alcohol addiction show a number of transient or persistent neurological and psychiatric deficits. The complexity of these brain alterations suggests that several brain areas are involved, although the definition of the brain alteration patterns is not yet accomplished. Aim: To determine brain atrophy patterns in patients with alcohol dependence. Methods: Voxel-based morphometry (VBM) of grey matter (GM) and white matter (WM) was performed in 22 patients with alcohol dependence and in 22 healthy controls matched for age and sex. Results: In patients with alcohol dependence, VBM of GM revealed a significant decrease in density (p<0.001) in the precentral gyrus, middle frontal gyrus, insular cortex, dorsal hippocampus, anterior thalamus and cerebellum compared with controls. Reduced density of WM was found in the periventricular area, pons and cerebellar pedunculi in patients with alcohol addiction. Conclusions: Our findings provide evidence that alcohol addiction is associated with altered density of GM and WM of specific brain regions. This supports the assumption that alcohol dependence is associated with both local GM dysfunction and altered brain connectivity. Also, VBM is an effective tool for in vivo investigation of cerebral atrophy in patients with alcohol addiction.